Differential diagnosis and morphological and functional characteristics of atrial myxoma - O. A. Sukhorukova; A. A. Parno; V. V. Mayer; A. E. Ali-Riza; E. V. Semichev (Российский кардиологический журнал, 2020)
Right atrial myxoma is one of the rare diseases in cardiology practice. It is accompanied by an unclear clinical picture, and in most cases is asymptomatic and is an incidental finding. The article is devoted to the clinical observation of primary cardiac tumor and the difficulties of its differential diagnosis.Patient T, 58 years old, was hospitalized in a respiratory medicine center with complaints of cough with viscous sputum, weakness, fatigue, loss of appetite, shortness of breath on exertion, weight loss and sweating at night. The preliminary diagnosis was an exacerbation of chronic bronchitis. Then a space-occupying mass in the right atrium was revealed. Computed tomography imaging identified a bilateral pulmonary embolism. In the cardiac surgery department, surgical removal of the right atrial myxoma was performed.The diagnosis of right atrial myxoma was established by echocardiography, confirmed macroscopically during surgery, and then by histological verification.